Pengembangan Berkelanjutan Kawasan Karst sebagai Kawasan Hutan Konservasi: Pendekatan Potensi Geologi di Daerah Ratatotok, Sulawesi Utara - Harman Rachmadhan; Febryanto Masulili; Alvaro Najoan; Regina Janis; Gresyella Pesik (Universitas Halu Oleo, 2024)
The development of the karst region in Ratatotok, North Sulawesi, requires an integrated geological approach for effective conservation forest management. This research utilizes geospatial analysis and geological mapping to understand the geological dynamics and geohazard potential in the area. Six main rock units were identified: Andesite-Basalt Lava, Marl Limestone, Crystalline Limestone, Basalt Breccia, Sandstone, and Alluvial Deposits. The complex geological structures, including fractures and faults with a main orientation of Southeast-Northwest, reflect the regional tectonic influence from the subduction between the Pacific Plate and the Indo-Australian Plate, specifically the Molucca Sea Plate. Drainage pattern maps reveal two main flow directions influenced by the structures, with intense erosion. The geomorphological map depicts four primary landforms: Denudational Karst Slopes, Denudational Hills, Karst Alluvium Plains, and Karst Valleys, reflecting karst activity in the landscape. The geohazard risk map shows potential geohazards such as landslides, rock falls, and subsidence, indicated based on the overlay of lithology, slope, and geological structures. Forest conservation and ecotourism in this area offer opportunities, with karst caves as a major attraction. Ecotourism management must adhere to sustainability principles to prevent environmental damage. Management strategies include establishing tourism and conservation zones and involving local communities in sustainable management. Partnerships with stakeholders and routine monitoring are crucial for the success of conservation and development in the Ratatotok karst area.